STRATEGI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA JENJANG SEKOLAH DASAR - Mumu Zainal Mutaqin (LPPM Universitas Bina Bangsa, 2023)
This study aims to explore the potential of Islamic religious education teachers at the elementary school level because their implementation only pays attention to cognitive aspects rather than growing awareness of Islamic religious values. as well as neglecting the development of affective and conative volutive aspects, namely the will and commitment to practice the values of religious teachings. The substance of Islamic religious education is manifested in speech, attitudes and behavior, but until now learning has not affected the daily behavior of students. The research method used in this research is a qualitative approach with library research methods. Literature study is an activity that cannot be separated from research. Data collection techniques in library research can be done by reviewing books, journal articles, research reports, websites, newspapers, and magazines. Islamic religious education learning strategies can be implemented by applying an emotional atmosphere and social relations approach in classroom management. This approach is based on the views of clinical and counseling psychology. Because classroom management is a process of creating an emotional atmosphere and positive social relations in the classroom. This strategy recognizes the conditions of psychological development. The next strategy, using the media, is to include a brief description of the material being studied on power point and then provide a detailed explanation verbally. This is done when the teacher conducts learning in large or classical groups